Monolingualism or multiple versions for Erasmus+ Guidelines? Incompatibilities and utopia. - HATZIDAKI, ELISA (International Journal of Language, Translation and Intercultural Communication, 2016)
Since the ECSC Treaty signed in Paris in 1951, marking the beginning of the commun destiny of the first international integration organization until the most recent decisions, such as the single currency or the immigration policies, it is a matter of fact that European Union progresses only with harmonious dialogue and joint actions, built on mutual respect of others’ differences. Nowadays, in the rapidly changing societies, financial concurrence and geopolitical stakes together with arrogance, or dominance, often outweigh the plurilingual communication, thereby leading to worries about linguistic equality within the Union; hence, the subject of the present stydy. Communication in this polyglottic supranational union should be based on an equal pattern, without what the impact of English as lingua franca[1] may be contested and criticised. This combined with the fact that translations are not fully compatible with the English text, implies that European Union does not always resonate at the same frequencies. [1] http://www.euractiv.fr/section/langues-culture/news/l-anglais-se-confirme-comme-la-lingua-franca-de-l-europe/